Undergraduate business students' learning experiences during the COVID-19 pandemic: Insights for remediation of future disruption. Issue 1 (March 2023) - Fang, Jim; Pechenkina, Ekaterina; Rayner, Gerry M.
Abstract: Despite the rapid proliferation of literature exploring student learning during the COVID-19 pandemic, little has been published about its impacts on business undergraduates during the pivots to remote teaching and learning. There is a particular lack of insight and guidance for business schools to optimise program delivery post-COVID or for similar future disruptions. This case study explored the learning experiences of undergraduate business students during the COVID-19 pandemic, drawing insights from an Australian university located in the state of Victoria, one of the 'most locked down places in the world'. Thematic analysis identified the following emergent themes: (1) Mixed student experiences and perceptions of online learning upon transitioning into lockdown/emergency remote teaching/learning; (2) Limited connections and interactions amongst student-student(s) and student-lecturer/tutor; (3) Perceived ineffective online teaching delivery; (4) Positive aspects of emergency remote learning; (5) Adequacy of support for learning during lockdowns; (6) Preferences for post-COVID-19 learning. The outcomes provide proactive signposts for university educators wishing to improve student engagement and learning, and delivery of business undergraduate programs for a post-COVID world as well as future pandemic and similar disruption settings. Highlights: Qualitative case study exploring the learning experiences of undergraduate business students during COVID-19 pandemic. Unique challenges, barriers and enablers of online learning during COVID-19 pandemic. Students preferring blended learning for post-COVID learning. Guide for university business schools wishing to improve student engagement and learning for a post-COVID world and future pandemic disruption settings.